Evaluation of the Follow-Up Resolution of Audit Findings at the Bontang City Inspectorate - Dafandika Pramudya; Annisa Yuniar Larasati (Universitas KH. Abdul Chalim Mojokerto, 2026)
Based on qualitative research on the follow-up of audit findings in Bontang City, the effectiveness of the current system is evaluated through four key components. From the input perspective, the mechanism is supported by audit recommendations, the Mayor Regulation of Bontang (Perwali) No. 10/2021, and the implementation of the SIENDUT application. In terms of process, monitoring is conducted periodically through the Annual Supervision Work Plan (PKPT) and regular coordination between the Inspectorate and Regional Government Agencies (OPD). Although the quantitative output indicates a positive achievement rate of 91% as of December 2025, challenges remain, particularly in financial administration, which requires a longer completion period due to procedural and verification requirements. As feedback for future system improvement, the study reveals that follow-up completion is often limited to fulfilling administrative compliance rather than becoming an embedded organizational work culture. Technical constraints, such as differing interpretations of audit findings and suboptimal data synchronization within the SIENDUT application, are notable concerns. Strengthened leadership commitment and early involvement of OPDs in the formulation of corrective action plans are essential to ensure that the system not only achieves numerical targets but also sustainably improves the quality of organizational governance.